Analisis Profil Kekuatan Otot Upper Body dan Lower Body Pemain SSB Buana Putra Pare U-12 - Muhammad Rizky Risalatullah; Muhammad Yanuar Rizky; Puspodari Puspodari (Mutiara Pendidikan dan Olahraga, 2026)
This study aims to determine the profile of upper body and lower body muscle strength in soccer players at SSB Buana Putra Pare, aged U-12. This research uses a quantitative approach with a descriptive design. The research population consisted of 15 players, and the entire population was used as a sample using a saturated sampling technique (total sampling). Data collection was carried out using the 30-second Push Up Test, 30-second Sit Up Test, Handgrip Dynamometer, Back Dynamometer, Leg Dynamometer, Nordic Hamstring Test, and Squat Test. Data analysis used descriptive statistics including minimum, maximum, mean, standard deviation, frequency distribution, and percentage. Categorization was determined using group norms according to Azwar (2019). The results showed that for the upper body component, the average value of arm muscle strength was 16.27 times, abdominal muscle strength was 18.67 times, grip strength was 21.80 kg, and back muscle strength was 46.73 kg. For the lower body component, the average value of leg muscle strength was 89.40 kg, hamstring muscle strength was 14.27 repetitions, and thigh muscle strength was 30.00 repetitions. Based on the Azwar (2019) group norms, the overall upper body and lower body muscle strength profile of the U-12 SSB Buana Putra Pare players is in the moderate category. These findings can be used by coaches as baseline data to design more systematic physical conditioning programs.